Culture media for clinical bacteriology in low- and middle-income countries: challenges, best practices for preparation and recommendations for improved access. (October 2021) - Orekan, Jeanne; Barbé, Barbara; Oeng, Sopheap; Ronat, Jean-Baptiste; Letchford, Joanne; Jacobs, Jan; Affolabi, Dissou; Hardy, Liselotte
Abstract: Background: Culture media are fundamental in clinical microbiology. In laboratories in low- and middle-income countries (LMICs), they are mostly prepared in-house, which is challenging. Objectives: This narrative review describes challenges related to culture media in LMICs, compiles best practices for in-house media preparation, gives recommendations to improve access to quality-assured culture media products in LMICs and formulates outstanding questions for further research. Sources: Scientific literature was searched using PubMed and predefined MeSH terms. In addition, grey literature was screened, including manufacturer's websites and manuals as well as microbiology textbooks. Content: Bacteriology laboratories in LMICs often face challenges at multiple levels: lack of clean water and uninterrupted power supply, high environmental temperatures and humidity, dust, inexperienced and poorly trained staff, and a variable supply of consumables (often of poor quality). To deal with this at a base level, one should be very careful in selecting culture media. It is recommended to look for products supported by the national reference laboratory that are being distributed by an in-country supplier. Correct storage is key, as is appropriate preparation and waste management. Centralized media acquisition has been advocated for LMICs, a role that can be taken up by the national reference laboratories, next to guidance and support of the local laboratories. In addition, there is an important role in tropicalization and customization of culture media formulations for private in vitro diagnostic manufacturers, who are often still unfamiliar with the LMIC market and the plethora of bacteriology products. Implication: The present narrative review will assist clinical microbiology laboratories in LMICs to establish best practices for handling culture media by defining quality, regulatory and research paths.